Effects of High Gas Flow Rates on the Standard 10 cm x 10 cm GEM Prototype - Kiadtisak Saenboonruang (Science Faculty of Chiang Mai University, 2019)
The Gas Electron Multiplier (GEM) detector is one of promising particle detectors nowadays. With its excellences in spatial resolution, high rate detection capabilities, and flexibility in designs, the GEM detector has been utilized in various applications. Since the GEM detector has gas flowing throughout the detector during the operation, properties of gas could play a major role in defining the detector’s performances. This article reports the study of the effects of high gas flow rates (3.0, 4.5, 7.5, 10.5 L/hr) on the 10 cm ´ 10 cm GEM prototype using Am-241 as a gamma source. The results show that, because of the design and configuration of the GEM prototype, different high flow rates does not significantly affect the uniformity and signal amplification properties of the GEM detector. These results are consistent with the gas flow simulation using COMSOL Multiphysics, which shows relatively uniform gas distribution over the active area of the detector for all flow rates. However, further investigations are needed for other designs and configurations.